Surface‐Plasmon‐Enhanced Perovskite Light‐Emitting Diodes. Issue 30 (23rd June 2020) - Gu, Lianghui; Wen, Kaichuan; Peng, Qiming; Huang, Wei; Wang, Jianpu
Abstract: Perovskite light‐emitting diodes (PeLEDs) have attracted considerable attention because of their potential in display and lighting applications. To promote commercialization of PeLEDs, it is important to improve the external quantum efficiency of the devices, which depends on their internal quantum efficiency (IQE) and light extraction efficiency. Optical simulations have revealed that 20–50% of the light generated in the device will be lost to surface plasmon (SP) modes formed in the metal/dielectric interfaces. Therefore, extracting the optical energy in SP modes to the air will greatly increase the light extraction efficiency of PeLEDs. In addition, the SPs can accelerate radiative recombination of the emitter via near‐field effects. Thus, the IQE of a PeLED can also be enhanced by SP manipulation. In this review, first, general concepts of the SPs and how they can enhance the efficiency of LEDs are introduced. Then recent progresses in SP‐enhanced emission of perovskite films and LEDs are systematically reviewed. After that, the challenges and opportunities of the SP‐enhanced PeLEDs are shown, followed by an outlook of further development of the SPs in perovskite optoelectronic devices. Abstract : Recent progress in luminescence enhancement in metal halide perovskite light‐emitting materials and devices through the management of surface plasmons is reviewed. This can be achieved by means of either increased light extraction efficiency or enhanced radiative recombination rates. In addition, challenges and opportunities for the further development of surface‐plasmon‐enhanced perovskite light‐emitting diodes are outlined.